Photocatalysis-activated SR-AOP over PDINH/MIL-88A(Fe) composites for boosted chloroquine phosphate degradation: Performance, mechanism, pathway and DFT calculations - Xiao-Hong Yi; Ji, Haodong; Chong-Chen Wang; Yang Li; Yu-Hang Li; Chen Zhao; Ao Wang; Huifen Fu; Peng Wang; Xu Zhao; Liu, Wen (Applied Catalysis B: Environmental, 2021)
PDINH/MIL-88A(Fe) composites (PxMy) were fabricated from MIL-88A(Fe) and perylene-34,910-tetracarboxylic diimide (PDINH) via facile ball-milling strategy. The optimum P25M175 exhibited outstanding degradation performance toward chloroquine phosphate (CQ) by activating peroxydisulfate (PDS) under low power LED visible light. The synergistic effects of photocatalytic activations of PDS via the direct electron transfer PDS activation over P25M175 and indirect electron transfer PDS activation over pristine MIL-88A contributed to the boosted CQ degradation efficiency. The active species capture experimental data and electron spin resonance (ESR) determinations revealed that both active radicals (like SO4−, OH, O2−, h+) and nonradical singlet oxygen (1O2) participated in the CQ decomposition. The CQ degradation pathways and the toxicity evaluation of the intermediates were proposed based on LC–MS determination and DFT calculation. Also, P25M175 demonstrated good reusability and stability. The findings within this work offered deep insights into the mechanisms of organic pollutants degradation via photocatalysis-activated SR-AOP over Fe-MOF photocatalyst.
Keywords: Chloroquine phosphate; Degradation pathways; DFT calculation; Metal-organic framework; Sulfate radical-advanced oxidation process